Relationship between Sports Participation and Academic Discipline in Middle School Students in Egypt - Hassan, Mohamed (International Journal of Physical Education, Recreation and Sports, 2024)
Purpose: The aim of the study was to analyze the relationship between sports participation and academic discipline in middle school students in Egypt. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on college athletes in Malaysia reveals that regular physical exercise significantly improves sleep quality by increasing sleep duration and efficiency. Exercise reduces sleep latency, helping athletes fall asleep faster, and enhances deep sleep stages crucial for recovery. Additionally, physical activity aids in managing stress and anxiety, which are linked to poor sleep. However, the impact of exercise can vary depending on its intensity and timing. Unique Contribution to Theory, Practice and Policy: Self-determination theory (SDT), social cognitive theory (SCT) & achievement goal theory (AGT) may be used to anchor future studies on the relationship between sports participation and academic discipline in middle school students in Egypt. Schools should implement structured sports programs that emphasize not only physical skills but also the development of discipline, teamwork, and time management. Schools should adopt policies that promote the integration of sports and academics, ensuring that sports participation is not viewed as a distraction but as a complementary activity that enhances academic discipline.